Exploração racional da rizosfera de Senna spectabilis: interações entre as bactérias Pseudoxanthomonas indica e Shigella sp. - Trindade, Roberth Nascimento da [UNESP] (2016)
The discovery of new bioactive molecules has been the big target to over the years the chemistry of natural products, particularly micro-organisms has been shown to be an important source of discovery of new drugs. A wide range of compounds from microbial organisms are reported in the literature, however, recent research shows that these micro-organisms can undergo induction by certain external, chemical or physical agents, through defense mechanisms or even the existing mutualism on a particular medium, producing new chemical structures, which until then had silenced their biosynthetic route due to methodologies patterns of isolated farming. Through use of mixed cultures of bacteria, this study provides knowledge of the relationship between Pseudoxanthomonas indica and Shigella sp., Both from the rhizosphere of Senna spectabilis. For this, bacteria were grown in liquid Czapek broth cultivation being conducted the study of the growth of bacteria and production of metabolites against time, with a view to maximizing results and greater induction of chemical compounds. The use of analytics quickly and efficiently analyzes such as high-performance liquid chromatography tools (HPLC) associated with high resolution mass spectrometry (HRMS) enabled the obtaining of the chromatographic profile of microorganisms studied in mixed and single culture, and you can to observe the existence of chemical compounds produced only in co-culture demonstrated the potential of the approach used.